Methodological approach for strategic objectives in planning public sector - Andía Valencia, Walter (2016)
This article is based on the analysis of the strategic objectives set in the plans of the various local, regional and national public sector institutions, in order to determine the amount and quality objectives in drafting them; also proposing methodological improvements for this purpose.